MEDIA EDUKASI DIABETES MELITUS BERBASIS MOTION GRAPHIC - Marthana Yusa, I Made; Suarya Putra, I Nyoman Agus; Ayu Anggraini, Sintia (Kartala, 2022)
This article reveals the process of designing motion graphic-based educational media that conveys important things that the audience must discovered regarding the prevention and medical treatment procedure of diabetes melitus. Data regarding the need for media formats, diabetes melitus, models and communication approaches were collected by means of observation, documentation, interviews, literature study and documentation in the preliminary design or pre-production process. Based on the content analysis and the need for media formats, it was decided that educational media was realized in motion graphic format with an emphasis on visual communication approach, especially to put forward the iconic aspects to achieve effective understanding of information. This motion graphic-based educational media was tested at the Rumah Sakit Angkatan Darat Tk.II Udayana. The test results reveal that educational media has a success rate of 80% in terms of motion graphics and content quality, and 100% in audio quality, so it is recommended for distribution.